Digital skills and virtual work in the future of labor migration: insights into the experience of Uzbekistan in Central Asia - Bekzod Musaev; Ikhtiyor Bekov; Goran Bandov (Department of Government Studies, Universitas Muhammadiyah Makassar, 2026)
This article examines how digital skills and virtual employment are reshaping labor migration patterns, with a focus on Uzbekistan’s evolving experience within Central Asia. Drawing on comparative legal analysis and secondary statistical sources, the study traces the shift from predominantly physical mobility toward digitally mediated cross-border work facilitated by online labor platforms. Evidence from the Online Labour Index shows that demand for virtual labor is concentrated in high-income economies, while supply is generated largely by developing countries, reflecting an emerging digital division of labor. The article analyzes the implications of artificial intelligence, automation, and telework for migrant workers and assesses Uzbekistan’s policy responses, including vocational upskilling, WorldSkills standards, and pre-migration preparation. The findings suggest that targeted digital skills development, streamlined recognition of qualifications, and alignment of training with global standards can enhance the competitiveness of Uzbek workers in remote labor markets. The article contribute for recognizing “virtual labor migration” within international legal frameworks and integrating remote-work preparation into national workforce strategies to promote inclusive growth and social resilience.